Mobility during the neolithic and bronze age in northern ireland explored using strontium isotope analysis of cremated human bone. Issue 3 (9th April 2016) - Snoeck, Christophe; Pouncett, John; Ramsey, Greer; Meighan, Ian G.; Mattielli, Nadine; Goderis, Steven; Lee‐Thorp, Julia A.; Schulting, Rick J.
ABSTRACT: Objectives: As many individuals were cremated in Neolithic and Bronze Age Ireland, they have not featured in investigations of individual mobility using strontium isotope analysis. Here, we build on recent experiments demonstrating excellent preservation of biogenic 87 Sr/ 86 Sr in calcined bone to explore mobility in prehistoric Northern Ireland. Materials and Methods: A novel method of strontium isotope analysis is applied to calcined bone alongside measurements on tooth enamel to human remains from five Neolithic and Bronze Age sites in Northern Ireland. We systematically sampled modern vegetation around each site to characterize biologically available strontium, and from this calculated expected values for humans consuming foods taken from within 1, 5, 10 and 20 Km catchments. This provides a more nuanced way of assessing human use of the landscape and mobility than the 'local' vs. 'non‐local' dichotomy that is often employed. Results: The results of this study 1) provide further support for the reliability of strontium isotope analysis on calcined bone, and 2) demonstrate that it is possible to identify isotopic differences between individuals buried at the same site, with some consuming food grown locally (within 1‐5 Km) while others clearly consumed food from up to 50 Km away from their burial place. Discussion: Hints of patterning emerge in spite of small sample numbers. At Ballynahatty, for instance, those represented by unburnt remains appear to have consumed food growing locally, while those represented by cremated remains did not. Furthermore, it appears that some individuals from Ballynahatty, Annaghmare and Clontygora either moved in the last few years of their life or their cremated remains were brought to the site. These results offer new insights into the choice behind coterminous cremation and inhumation rites in the Neolithic. Am J Phys Anthropol 160:397–413, 2016. © 2016 Wiley Periodicals, Inc.